FAKTOR SOSIAL BUDAYA DALAMA PENETAPAN HUKUM PRIVAT DALAM ISLAM - Dr. Andi Herawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Social culture is everything created by man with the mind and conscience of gratitude for the life of society. Medium private law (civil) is the law governing family relationships, including marriage, custody, transfer of assets, endowments, grants, sadaqah, and others. The Islamic law can not be separated from social realities, because Islamic law live and develop along with the development and social change. Thus, Islamic law can not be separated from sociological aspects in the formation and development. Sociological aspects of it have been incorporated in the form of al-nuzul asbab, asbab al-wurud, fikhi (the result of reasoning), fatwa scholars, court jurisprudence, and legislation.